2020
DOI: 10.1080/02640414.2020.1860360
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of impairment measures to inform an evidence-based classification structure in RaceRunning, a new World Para Athletics event for athletes with hypertonia, ataxia or athetosis

Abstract: RaceRunning enables athletes with limited or no walking ability to propel themselves independently using a three-wheeled frame that has a saddle, handle bars and a chest plate. For RaceRunning to be included as a para athletics event, an evidence-based classification system is required. This study assessed the impact of trunk control and lower limb impairment measures on RaceRunning performance and evaluated whether clusters analysis of these impairment measures produce a valid classification structure for Rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Subsequently, Beckman et al (2016) explored the relationships between (impaired) strength and running performance in 13 participants with eligible impairments of hypertonia, athetosis and, ataxia, but they did not find significant associations between these measurements. However, other studies with para-athletes with more severe impairment related to brain injuries reported significant associations among spasticity scores and speed in Race Running, suggesting the impact of the impairment on the sport-specific performance ( van der Linden et al, 2018 , 2020 ). The significant strength of the association (i.e., trivial-to-moderate) between spasticity and the physical tests obtained in the present study suggests a low impact of lower limbs’ spasticity on sports performance in para-footballers with a high level of proficiency (i.e., international-level and GMFCS Level 1).…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Subsequently, Beckman et al (2016) explored the relationships between (impaired) strength and running performance in 13 participants with eligible impairments of hypertonia, athetosis and, ataxia, but they did not find significant associations between these measurements. However, other studies with para-athletes with more severe impairment related to brain injuries reported significant associations among spasticity scores and speed in Race Running, suggesting the impact of the impairment on the sport-specific performance ( van der Linden et al, 2018 , 2020 ). The significant strength of the association (i.e., trivial-to-moderate) between spasticity and the physical tests obtained in the present study suggests a low impact of lower limbs’ spasticity on sports performance in para-footballers with a high level of proficiency (i.e., international-level and GMFCS Level 1).…”
Section: Discussionmentioning
confidence: 84%
“…According to the catch presence and the degree of resistance generated during the rapid passive stretching movement, a rating ordinal score was assigned to each evaluated muscle group, where 0 indicated no spasticity or catch on rapid passive movement and four affected part(s) rigid contracture segment but moves on slow passive movement ( Love et al, 2016 ). Even though the Modified Ashworth Scale is commonly utilized for both clinical and para-sport settings, the ASAS has been used in Paralympic sports which involve participants with CP, such as Race Running ( van der Linden et al, 2020 ), Boccia ( Reina et al, 2015 ), Para-cycling ( Liljedahl et al, 2020 ), and Para-taekwondo ( Para-Taekwondo, 2021 ). Additionally, ASAS was also utilized in adults with brain injuries ( Calame and Singer, 2015 ), and showed good inter-rater reliability (weighted kappa = 0.87; ICC = 0.88) in the assessment of children with CP ( Love et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations